2005
DOI: 10.2337/diacare.28.4.838
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Glomerular Filtration Rate in Diabetic Subjects

Abstract: OBJECTIVE -The Cockcroft-Gault formula is recommended for the evaluation of renal function in diabetic patients. The more recent Modification of Diet in Renal Disease (MDRD) study equation seems more accurate, but it has not been validated in diabetic patients. This study compares the two methods.RESEARCH DESIGN AND METHODS -In 160 diabetic patients, we compared the Cockcroft-Gault formula and MDRD equation estimations to glomerular filtration rates (GFRs) measured by an isotopic method ( 51 Cr-EDTA) by correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
102
2
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(120 citation statements)
references
References 37 publications
6
102
2
10
Order By: Relevance
“…When comparing both equations, the GFR values that were obtained with the C-G method were higher, and the differences were larger with higher BMI values. Other studies have shown that, in the presence of obesity/ overweight, the C-G method overestimates GFR and consider the MDRD equation, especially in cases of reduced GFR, to be more accurate (18,19).In the Spanish population pilot study, the prevalence of GFR Ͻ60 ml/m per 1.73 m 2 was 5.1% (20), similar to that (5% of the population) performed in Ͼ500,000 patients in a Canadian population (21). However, when patients with hypertension are studied, there is a greater prevalence of RI.…”
mentioning
confidence: 99%
“…When comparing both equations, the GFR values that were obtained with the C-G method were higher, and the differences were larger with higher BMI values. Other studies have shown that, in the presence of obesity/ overweight, the C-G method overestimates GFR and consider the MDRD equation, especially in cases of reduced GFR, to be more accurate (18,19).In the Spanish population pilot study, the prevalence of GFR Ͻ60 ml/m per 1.73 m 2 was 5.1% (20), similar to that (5% of the population) performed in Ͼ500,000 patients in a Canadian population (21). However, when patients with hypertension are studied, there is a greater prevalence of RI.…”
mentioning
confidence: 99%
“…Neither of these equations, based on serum creatinine, is highly predictive of GFR. The Cockcroft-Gault equation is less accurate (4), biased by body weight (5), and less robust in patients with poor glycemic control (6). The simplified MDRD equation allows renal function to be classified with acceptable precision and requires only usual information about the patient.…”
mentioning
confidence: 99%
“…Using the NHANES III data, a GFR Ͻ60 ml/min is estimated to be present in 26% of patients who are Ն70 yr of age (14). Finally, diabetes currently affects 194 million people worldwide, and the number of affected individuals in future years is expected to be significantly greater (10,15). It is estimated that diabetic nephropathy affects 25 to 40% of patients with this disease (16).…”
mentioning
confidence: 99%